Gender Role in the Victorian Era a Case Study of Charlotte Bronte's The Professor - Abdessatar, Boukhezna, Aida Naoual (جامعة الوادي University of Eloued, 2019)
تهدف هذه الأطروحة إلى دراسة دور الجنس في العهد والأدب الفيكتوري الذي يصور مكانة المرأة في المجتمع الطبقي. في رواية الأستاذ, قامت شارلوت برونتي بنقل رحلة المرأة لتحقيق الاستقلالية والمساواة. كما تهدف الدراسة الحالية أيضا لتحليل ادوار الجنس في العهد الفيكتوري و طريقة النساء في رفضهن لدورهن الذي يقتصر على كونهن زوجات وربّات بيوت فقط. وللوصول إلى الهدف المنشود قد تمت دراسة تحليلية لرواية الأستاذ والتي اعتمدت على نظريتين: النظرية النسوية و نظرية الجنس وبالتحديد النظرية البيولوجية والهيكلية. وكنتيجة لذلك فإن أدوار كلا الجنسين قد تم التعبير عنها من خلال وجهة نظر البطل ومن وجهة نظر الكاتب التي جعلت كلا من البطل والنساء اللواتي يقابلهن يتحدون القوانين الفيكتورية المطبقة في المجتمع. لتنتهي الدراسة بمحاولة المرأة تحقيق حريتها رغم عدم نجاحها الكامل. The present research deals with the gender roles during the Victorian Era and the literature produced during the period that reflects the social status of women in the patriarchal society. In The Professor, Charlotte Bronte highlights the female journey towards the independence and equality. The study under investigation aims at investigating the gender roles during the Victorian Era and the way women tended to reject the limitation of their role to housewives and mothers. To reach this objective, we conducted an analytical study depending on two different theories, feminism and gender role theories namely; biological and structural. Thus, the gender role presented through the protagonist’s eyes challenges the Victorian imposed roles, but it still did not make women free and independent.
Keywords: دور الجنس, الأستاذ, المجتمع الطبقي, العهد الفيكتوري.; Gender role, The Professor, patriarchal society, Victorian Era